The Hypoglycemic Effect of JinQi Jiangtang Tablets Is Partially Dependent on the Palmatine-Induced Activation of the Fibroblast Growth Factor Receptor 1 Signaling Pathway - Li, Siming; Li, Xiaoling; Wang, HeMeng; Jia, Xinhang; Mao, Haoyang; Dong, Fangxin; Zhao, Tingting; Gao, Yuan; Zhang, Chen; Bai, Ruisong; Liu, Ruihao; Yan, Lijun; et al. (Frontiers in Pharmacology, 2022)
JinQi Jiangtang tablet (JQJTT) is a Chinese patent medicine that has been shown to be beneficial for patients with diabetes both preclinically and clinically; however, the molecular mechanism underlying the effects of JQJTT remains unclear. In this study, SPR fishing was employed to identify JQJTT constituent molecules that can specifically bind to FGFR1, leading to the retrieval of palmatine (PAL), a key active ingredient of JQJTT. In vivo and in vitro experiments demonstrated that PAL can significantly stimulate FGFR1 phosphorylation and upregulate GLUT-1 expression, thereby facilitating glucose uptake in IR HepG2 cells as well as alleviating hyperglycemia in diabetic mice. Our results revealed that PAL functions as an FGFR1 activator and that the hypoglycemic effect of JQJTT is partially dependent on the PAL-induced activation of the FGFR1 pathway. Additionally, this study contributed to the understanding of the pharmacodynamic basis and mechanism of action of JQJTT and provided a novel concept for future research on PAL.